SARS-CoV-2 and the safety margins of cell-based biological medicinal products. (November 2020) - Modrof, Jens; Kerschbaum, Astrid; Farcet, Maria R.; Niemeyer, Daniela; Corman, Victor M.; Kreil, Thomas R.
Abstract: With the pandemic emergence of SARS-CoV-2, the exposure of cell substrates used for manufacturing of medicines has become a possibility. Cell lines used in biomanufacturing were thus evaluated for their SARS-CoV-2 susceptibility, and the detection of SARS-CoV-2 in culture supernatants by routine adventitious virus testing of fermenter harvest tested.